DAF‐16 stabilizes the aging transcriptome and is activated in mid‐aged Caenorhabditis elegans to cope with internal stress. Issue 3 (17th February 2019) - Li, Shang‐Tong; Zhao, Han‐Qing; Zhang, Pan; Liang, Chung‐Yi; Zhang, Yan‐Ping; Hsu, Ao‐Lin; Dong, Meng‐Qiu
Abstract: The roles and regulatory mechanisms of transcriptome changes during aging are unclear. It has been proposed that the transcriptome suffers decay during aging owing to age‐associated down‐regulation of transcription factors. In this study, we characterized the role of a transcription factor DAF‐16, which is a highly conserved lifespan regulator, in the normal aging process of Caenorhabditis elegans . We found that DAF‐16 translocates into the nucleus in aged wild‐type worms and activates the expression of hundreds of genes in response to age‐associated cellular stress. Most of the age‐dependent DAF‐16 targets are different from the canonical DAF‐16 targets downstream of insulin signaling. This and other evidence suggest that activation of DAF‐16 during aging is distinct from activation of DAF‐16 due to reduced signaling from DAF‐2. Further analysis showed that it is due in part to a loss of proteostasis during aging. We also found that without daf‐16, dramatic gene expression changes occur as early as on adult day 2, indicating that DAF‐16 acts to stabilize the transcriptome during normal aging. Our results thus reveal that normal aging is not simply a process in which the gene expression program descends into chaos due to loss of regulatory activities; rather, there is active transcriptional regulation during aging.